Effects of bioactive fatty acid amide derivatives in zebrafish scale model of bone metabolism and disease. (February 2016) - Carnovali, M.; Ottria, R.; Pasqualetti, S.; Banfi, G.; Ciuffreda, P.; Mariotti, M.
Graphical abstract: Abstract: The endocannabinoid system (which includes fatty acid derivatives, receptors, and metabolizing enzymes) is involved in a variety of physiological processes, including bone metabolism in which it regulates the function of osteoblasts and osteoclasts, as well as differentiation of their precursors. The zebrafish ( Danio rerio ) provides a useful animal model for bone research since zebrafish bones develop rapidly and are anatomically similar to mammalian bones. Putative orthologues and paralogs of endocannabinoid genes have recently been identified in zebrafish, demonstrating the presence of cannabinoid type 1 (CB1) and type 2 (CB2) receptors with affinity to endocannabinoid ligands. To identify therapeutic molecules potentially useful in bone-related diseases, we evaluated the in vivo effects of exposure to long-chain fatty acid amides in adult zebrafish. Using a well-established zebrafish scale model, we found that anandamide and N -linoleoylethanolamine are able to stimulate bone formation by increasing alkaline phosphatase activity in physiological conditions. In addition, they prevent the alteration of bone markers in a prednisolone-induced osteoporosis model in adult zebrafish scales, whereas their esterified forms do not. These data suggest that long-chain fatty acid amides are involved in regulating bone metabolism in zebrafish scales and that the CB2 receptor is a key mediator in this process.